Application of geostatistical ore reserve evaluation techniques to optimise valuation of mining blocks at Beatrix Mine - Ashong, Emmanuel Tettey (My University, 1998)
This project report describes a geostatistical study undertaken on the Geozone 5 deposit at Beatrix Mine in the Free State. Geostatistical analysis of this deposit is described in considerable detail to illustrate the application of the method to a tabular-type deposit using Geostokos Toolkit, a computer software package developed b. Prof Isobel Clark. Comparison has been made between indicator kriging and lognormal kriging to establish which of the two geostatistical techniques will optimise the valuation of the Geozone 5 deposit. The mean absolute error (MAE) and mean square error (MSE) criteria, and the correlation between kriging estimates and actual values have been used as the basls for this comparison. The results show that lognorma kriging will improve the estimates of resources as a result of lower MAE and MSE values over indicator kriging. This reduction is further confirmed by a higher correlation coefficient for lognormal kriging estimates. The location of future additional exploratory drilling, particularly in the northern part of the deposit, should be guided by the range of influence of approximately 350 meters as established by the experlmenial semivariogram , since samples have no influence beyond this range value from their locations. This study has demonstrated that geostatistical techniques can be applied at the mine site to improve block estimates and also reduce block estimation variance as new data becomes available.
A project report submitted to the Faculty of Engineering, in partial fulfilment of the requirements for the degree of Master of Science in Engineering, University of the Witwatersrand. Johannesburg 1998.